Nationalism as Pawongan Reflection in King Tirian’s Characterization in C.S. Lewis’s The Last Battle - Ni Kadek Riska Aristyawati; Ni Komang Arie Suwastini; I Nyoman Pasek Hadi Saputra; I Putu Ngurah Wage Myartawan; Ni Nyoman Artini (International Journal of Language and Literature, 2026)
Literary works play an important role in instilling character values, including nationalism, but studies linking nationalist values ​​in Western literary works with Indonesian local wisdom are still limited. The character of King Tirian in The Last Battle has not been widely analysed as a representation of nationalism that can be reflected through the perspective of local wisdom. This study aims to analyse the value of nationalism as a reflection of the value of Pawongan in the characterisation of King Tirian in the novel The Last Battle by C.S. Lewis. This research is a qualitative interpretative study. The subject of this study is the story of The Chronicles of Narnia: The Last Battle by C.S. Lewis. The researcher acted as the main instrument with data collection techniques in the form of in-depth reading and recording of events and dialogues. In contrast, data analysis used the interactive model of Miles, Huberman, and Saldana, which includes data condensation, data presentation, and cyclic drawing of conclusions. The results of the study show that King Tirian internalises nationalistic attitudes by protecting the territory of Narnia, having positive leadership traits, and showing a willingness to sacrifice for the people and Narnia. This behaviour reflects a spirit of nationalism that aligns with the principle of Pawongan in the Tri Hita Karana concept, which emphasises the importance of harmony among human beings. This research implies that literary works can be a means of depicting moral and national values ​​that align with local wisdom and character education.